Structural analysis of capsular polysaccharides produced by some emerging Klebsiella pneumoniae serotypes - Mfana, Siwaphiwe (Department of Chemistry, 2025)
Klebsiella pneumoniae (K. pneumoniae), a Gram-negative pathogenic bacterium, is a leading cause of neonatal sepsis in low- and middle-income countries (LMICs). Due to rapidly increasing anti-microbial resistance (AMR), it has been ranked among the “critical-priority 1” pathogens to human health by the World Health Organisation (WHO). K. pneumoniae produces a capsular polysaccharide (CPS or Kantigen), which constitutes an important virulence factor and a potential vaccine antigen. To date, there are up to 77 known distinct K. pneumoniae K-antigen serotypes, that have been classified through serotyping. Furthermore, there are additional K-locus (KL) serotypes that have been recently identified using genotyping. This project involved the characterisation and structural elucidation of the CPS repeating unit (RU) structures, known as chemotyping, of four emerging clinically significant strains of K. pneumoniae, which were identified through genotyping as novel serotypes: KL102; KL112; KL122; and KL107. NMR spectroscopy provides a non-destructive method for the structural elucidation of polysaccharides on relatively small amounts of samples. A combination of 1D and 2D homo and heteronuclear NMR experiments can be used to determine the monosaccharide composition, anomeric configurations ( or ), linkage positions and sequence of residues in the polysaccharide RU. NMR can also identify the presence and positions of non-carbohydrate substituents including O-acetyl and pyruvate groups. Complete NMR characterisation and structural elucidation was successfully achieved for all four capsular polysaccharides investigated. Their proposed RU structures were compared to those of known K. pneumoniae K-antigens, using a database that was constructed during this investigation, to confirm if they were novel serotypes. KL102 CPS has a novel hexasaccharide RU, made up of a trisaccharide backbone, and is doubly-branched with a disaccharide and a single terminal residue side chains, this can be categorised as a 3 + 2 + 1 RU type. KL112 CPS has a novel and unusual pentasaccharide RU, consisting of a disaccharide backbone chain and a trisaccharide side chain, categorised as a 2 + 3 RU type. KL122 CPS also has a novel hexasaccharide RU containing three uronic acids and is made up of a tetrasaccharide backbone chain with two terminal monosaccharide residues, thus a 4 + 1 + 1 RU type. In contrast, KL107 CPS was found to be identical to serotype K2, having a tetrasaccharide RU, with a trisaccharide backbone chain and a single terminal residue with Oacetylation on the branched backbone residues. The diagnostic NMR data acquired for these CPSs can be used for serotype identity testing, and to monitor the structures of K-antigens during the process of glycoconjugate vaccine development